In Search of Namibian Independence : the Limitations of the United Nations. - Rocha, Geisa Maria (Routledge, 2018)
Focusing on the Namibian issue and how it has been handled in the United Nations since 1945, this book discusses the limitations of the UN as a political institution and assesses its ability to manage crises and control conflicts. The UN was established to help maintain international peace and security; since its founding, however, the independence and sovereignty of member states has come to take precedence over the organization's original goals. As a result, contends Ms. Rocha, the UN may be viewed as a passive arena where political actors pursue their policies and priorities in response to the larger realities and forces governing world politics. In the case of Namibia, the UN simply cannot take significant action in expelling the illegal South African administration without the support of the few powerful members who provide it with resources. She concludes that the liberation of Namibia rests ultimately with the Namibian people themselves and the ability of SWAPO to intensify its armed struggle, thereby causing South Africa to consider its presence in Namibia more a liability than an asset.